The First Homozygous Family for Prothrombin G20210A Polymorphism Reported in Latin America (2009)
ABSTRACT: The 20210A allele of the prothrombin gene is associated with increased risk of venous thromboembolism. In this study, we described manifestations of thrombosis in four generations of a Colombian family, with four 20210A homozygous carriers and six 20210G/A heterozygous carriers for polymorphism as well as unrelated participants from the same population. The levels of prothrombin in the 20210A homozygote patients were higher than in the normal 20210G homozygotes (133 + 11% and 92.3 + 12.4%, respectively, P < .01) and the 20210G/A heterozygotes (133 + 11% vs. 114.8 + 24%, P < .05). About 2 out of 4 20210A homozygotes and 5 out of 6 20210G/A heterozygous members of this family did not have venous thromboembolism or any other thrombotic manifestation even though one of them had been exposed to thrombotic risk factors. Thus, we posit the effect of 20210A on the thrombotic phenotype in this family seems to be weak.